Status, biodiversity, and ecosystem services of seagrass habitats within the Coral Triangle in the western Pacific ocean - Al-Asif, Abdulla-; Kamal, Abu Hena Mustafa; Hamli, Hadi; Idris, Mohd Hanafi; Gerusu, Geoffery James; Ismail, Johan; Bhuiyan, Md Khurshid Alam; Abualreesh, Muyassar H.; Musa, Najiah; Wahid, Mohd Effendy Abd; Mishra, Manoranjan (Springer, 2022)
Area of the Coral Triangle (CT), namely Indonesia, Malaysia, Papua New Guinea, Philippines, Solomon Islands, and Timor-Leste, comprises 5.7 million km2 of the Pacific Ocean. It is one of the most bio-diverse marine eco-regions on the planet, as well as a global hotspot for seagrass species. Many sea creatures of this eco-region rely on the seagrass ecosystem, especially dugong species extensively (a total number of 2279 individuals), sea turtles (4–6 species), benthic organisms, and fish. Apart from these ecological services, carbon sequestration (2.6 billion Mg CO2 storage) by the seagrass ecosystem is considerably higher in comparison to terrestrial vegetation. In this paper, we scrutinized previously acknowledged seagrass species distribution, the associated fauna in seagrass meadows, the total carbon sequestration in the Coral Triangle, past and present research conducted on seagrass and other aspects, and major threats to seagrass ecosystems within this biogeographic region. Depending on their different locations, the six CT countries have a minimum of 10 to a maximum of 19 seagrass species that belong to four distinct families (Hydrocharitaceae, Cymodoceaceae, Zosteraceae, and Ruppiaceae) and cover almost 58,550.63‬ km2. While a total of 21 species of seagrass have been found throughout this eco-region, very little research has been conducted to assess the overall status of the ecosystems within this eco-region. Seagrass ecosystems and services from these habitats within the Coral Triangle are also associated with 100 million human inhabitants, who are supported directly or indirectly by the resources of this ecosystem. These inhabitants may cause considerable disturbance to seagrass ecosystems. For the long-term sustainable management and conservation of these ecosystems, two types of threats, namely local human activities and global transboundary issues including climate change, have been identified and need to be taken into consideration. In terms of human activities, local threats include water quality deterioration due to sewage and pollutant discharge, agricultural activities mainly from palm oil plantations, over-exploitation of seagrass-associated resources, sediment runoff, and destructive fishing practices. Global threats comprise macro and microplastics, sea-level rise due to climate change, global warming, and acidification. Further study of social, cultural, and economic interaction between the local inhabitants and seagrass ecosystems is highly recommended for assessing the ecological and economic contribution of this habitat to the human societies of the Coral Triangle. Despite their importance for human food services and the maintenance of the food web for marine and coastal animals, human activities have a negative impact on seagrass ecosystems around the world, particularly in the Coral Triangle.